Antibacterial activity of Blumea balsamifera leaf extracts from Aceh, Indonesia - MASYUDI MASYUDI; ANITA NOVIYANTI; MUHAMMAD RIDHWAN; SALFAUQI NURMAN; JAILANI JAILANI; ARMI ARMI; T. M. RAFSANJANI; SAID USMAN; MUHAMMAD HANAFIAH; MARLINA MARLINA (Society for Indonesian Biodiversity, 2023)
Abstract. Masyudi, Noviyanti A, Ridhwan M, Nurman S, Jailani, Armi, Rafsanjani TM, Usman S, Hanafiah M, Marlina. 2023. Antibacterial activity of Blumea balsamifera leaf extracts from Aceh, Indonesia. Biodiversitas 24: 4584-4589. Blumea balsamifera L. has long been used as traditional medicine by communities in Aceh, Indonesia and from various parts of the world. For generations, this plant has been believed to have properties to cure various diseases. The results of the GCMS analysis of B. balsamifera leaf from Aceh-Indonesia in the previous study contain various compounds for wound healing, including borneol, jasmoline, camphor, and caryophyllene. The present study aimed to analyze the antibacterial activity of B. balsamifera leaves from Aceh. The sample was taken from the village of Gunongpulo, South Aceh-Indonesia, and the extraction process was carried out using three different types of solvents: ethanol, ethyl acetate, and n-hexane. Three variations of the extract obtained were then tested for antibacterial against Staphylococcus aureus and Pseudomonas aeruginosa by analyzing the inhibitory of each extract. The results showed that the inhibition zone formed on S. aureus against ethanol extract was 2.4 mm, ethyl extract was 9.2 mm, and n-hexane extract was 2.3 mm. In comparison, the inhibition zone formed on P. aeruginosa against ethanol extract was 0 mm, ethyl extract was 9 mm, and n-hexane extract was 4.9 mm. Conclusion: B. balsamifera leaf extract from Aceh contains antibacterial, with the highest inhibition against S. aureus at 9.2 mm and Pseudomonas at 9.0 mm. It is recommended that in the process of extracting B. balsamifera leaves by maceration, the best solvent used is ethyl acetate.